A Review Study Of Cloud-Based M-Learning Factors In Developing Countries (Journal of the College of Basic Education, 2024)
A number of technologies have been used to assist and improve the use of e-learning. Recently, research has centered on developing collaborative and interactive cloud-based m-learning platforms. Cloud computing is the most recent initiative to supply computer resources as a service. Using an integrated strategy based on Cloud Computing may be a method to gain agility and rapid access to technology while also saving money at the institutional level. This research provides a review of cloud-based m-learning elements and implementations in developing nations, as well as insights on difficulties and advantages connected with cloud-based m-learning. This study reviews various planned cloud-based m-learning efforts, including their predicted advantages, difficulties, and obstacles. The study used a non-experimental, exploratory research design. This exploratory study includes an important inquiry of secondary data. The findings demonstrate that mobile cloud learning may provide cost-effectiveness, flexibility, and mobility to learning in underdeveloped nations. The usefulness of cloud-based m-learning is not yet obvious, but it deserves further attention. and it shows that the educational institutions in developing countries needs continued attention to get government support, Cloud-based m-learning in developing countries has seen modest development in recent years at various levels of education and mobile services.